Calibration of the Tide Gauge at King Edward Point, South Georgia Island, South Atlantic Ocean - TEFERLE, Felix Norman; HUNEGNAW, Addisu; Woodworth, P. L.; Foden, Peter R.; Williams, S. D. P.; Pugh, Jeffrey; Hibbert, Angela (2015)
In 2008 a new pressure tide gauge with Global Sea Level Observing System Number 187 was installed at King Edward Point (KEP), South Georgia Island, South Atlantic Ocean. This installation was carried out as part of the Antarctic Circumpolar Current Levels by Altimetry and Island Measurements (ACCLAIM) programme. In 2013 the KEP Geodetic Observatory was established in support of various scientific applications including the monitoring of vertical land movements at KEP. Currently, the observatory consists of two state-of-the-art Global Navigation Satellite System (GNSS) stations with local benchmark networks. This ties all benchmarks and the tide gauge into the International Terrestrial Reference Frame 2008, and allows the establishment of a local height datum in a global height system through the use of a global gravitational model. In 2014 a tide board was added to the tide gauge, which, together with the GNSS and levelling observations, now enables a calibration of the tide gauge. This will make it possible to include the KEP tide gauge in the Permanent Service for Mean Sea Level (PSMSL) database. In this study, we will present the results from the calibration of the tide gauge using the GNSS observations from the KEP Geodetic Observatory for the period from February 2013 to present, the levelling campaigns in 2013 and 2014, and geoid undulations derived from a seamless combination of the latest Gravity Observation Combination (GOCO) 05S and Earth Gravitational Model (EGM) 2008 models. New Geodetic Infrastructure and Reprocessed GPS Solutions for Sea Level, Climate and Geodynamics (GSCG)